PHYSICAL CHARACTER OF KAMPUNG SETU BABAKAN, SOUTH JAKARTA, AS BETAWI CULTURAL HERITAGE REGION - Yoana Wardana ; Basuki Dwisusanto (Riset Arsitektur (RISA), 2019)
Abstract- Setu Babakan town which is located in Srengseng Sawah political districts, Jagakarsa sub-district, South Jakarta, is a region of settlement that are established as Betawi cultural heritage. This research discusses about representation of Betawi culture physical characters in Setu Babakan town. Culture characters could be faded with the advent of times due to lifestyle that has changes, but it could also be adhere with the awareness of the importance of preserving the existing culture.  This study attempts to know how far do the Setu Babakan physical characters as Betawi culture heritage districts reflects the physical characters of Betawi native culture, so it can be found which physical characters that is still retained, that modificated, and that are totally changed. In addition, can also be found how many buildings which is still retaining the whole physical heritage of Betawi culture, which only retaining some of the physical heritage of Betawi culture, and which are not retaining the physical heritage of Betawi culture at all.  Scope of this study was conducted throughout the area of Setu Babakan town so that the data be more accurate and to represent the overall condition of the area. The interview and questionnaire distribution was conducted to 21 respondents (20 respondents wich are Betawi ethnic and 1 respondent which is not Betawi ethnic, aged between 23-67 years old, islamist, with 3/4/5/6/10 family members)and the management of Setu Babakan town (Pak Buhori) to complement the data obtained through literature study and field observation about physical characters (buildings and outdoor layouts) and non-physical characters (rituality, social activities, religious, economic, abstinence, lifestyle, and education) of Betawi culture in Setu Babakan town and the physical and nonphysical characters of Betawi native culture. Data from the respondents, interior photo of respondent’s house, and respondents photo have been permitted by the concerned parties to be published. The observation and recovery data was undertaken along January-march 2018. Physical characters data (existing condition) that was obtained through direct observation in the field are strengthened by matching it with the existing condition in google street to avoid mistakes/inadvertence in the process of field observation. Physical characters observation is conducted by seeing one by one building, to know the authenticity level of its physical characters of Betawi culture in every building. All of the observation results were recorded by doing mapping. This research is qualitative-quantitative research approach descriptive and cultural.  Analysis is conducted in descriptive and causal comparative approach qualitative-quantitative. The analysis begins by comparing the physical characters of Betawi native culture backed by the non-physical characters with physical characters of Betawi culture in Setu Babakan town backed by the non-physical characters. Then doing macro mapping (showing number of buildings that retained the overall of physical characters of Betawi culture, that retained some of them, and that totally changed) and micro mapping (showing which physical characters that still been retained, modificated, nor totally changed) to know how far did the physical characters of Setu Babakan town as Betawi culture heritage districts reflected the physical characters of Betawi native culture and to know the factors that influence it.  The research results show, the physical character application of Betawi culture in Setu Babakan town has faded, so it needs to be developed again. Not until 50% of the buildings retained the physical characters of Betawi culture.   Key Words: physical characters, Setu Babakan town, Betawi culture heritage districs, South Jakarta